Mycobiota in Chilean chilli Capsicum annuum L. used for production of Merkén - Costa, Jéssica (2020)
This work aims to provide the first study on the mycobiota present in Chilean pepper Capsicum annuum L. cv. Cacho de Cabra throughout the early production stages. Two hundred and forty berry fruits were sampled: 1) at the ripe fruits harvest day; 2) during drying; and 3) smoking processes. A total of 192 strains, encompassing 11 genera and 44 species, were identified through analysis of -tubulin (benA) gene and internal transcribed spacer of ribosomal DNA (ITS) region. All collection points showed samples with high fungal contamination, but the mycobiota composition varied as a result of different environmental conditions. Alternaria spp. and Fusarium spp. were predominantly isolated from fresh fruits of C. annuum. Penicillium spp. was the most frequent genus in all analysed points. Penicillium brevicompactum and P. crustosum were the most abundant species. Among Aspergillus, A. niger and A. flavus were dominant after the drying phase. In our study, none of the analysed strains of Penicillium (113) and Aspergillus (35) produced Ochratoxin A at detectable levels. The broad characterization of the fungal community of C. annuum carried out in this study, could be a guideline for future mycotoxin analyses performed directly on the pod. Understanding the role and dynamics of mycobiota and its relationship with the toxins present in this substrate, will be useful to establish and improve control measures considering the specificities of each point in the C. annuum production chain.